Literacy of Al-Qur'an Tahfidz's Teacher - Syafitri, Nur'ain; Sudiar, Nining; Hakim, Triono Dul (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2024)
The objective of this research is to assess the extent of Qur'anic literacy among tahfidz teachers in Pekanbaru City. The investigation employed mixed research methods, including observation, interviews, questionnaires, and record-keeping. The sample consisted of 52 instructors, while the population of this study was 108 tahfidz teachers. The study revealed that the researchers had a good understanding of the first of the six indicators of Qur’anic comprehension based on the interviews. The second indicator, which measures fluency in reading the Qur’an among tahfidz teachers in Pekanbaru City, scored a maximum of 1040 with a total percentage of 88.75%, indicating a very high level of literacy. The third metric assesses the accuracy of Qur’an reading among tahfidz teachers in Pekanbaru City. The literacy level of tahfidz instructors in Pekanbaru City is very high, with a maximum score of 1040 and a total percentage of 87.30%. The literacy level of tahfidz instructors in Pekanbaru City is very high, with a maximum score of 1040 and a total percentage of 87.30%. The fourth indicator assesses whether reading with makhorijul letters is appropriate for these instructors. The fifth criterion evaluates their capacity to compose Qur’anic verses in Pekanbaru City, with a minimum literacy level of 780 and a total percentage of 54.74%. The sixth indication of communication methods for tahfidz instructors in Pekanbaru City demonstrates a very strong literacy level, with a maximum score of 520 and a total percentage of 87.11%.